Identification of surface functional group on activated carbon from waste sago - Octolia Togibasa; Yane Oktovina Ansanay; Khaeriah Dahlan; Maya Erari (Journal of Physics: Theories and Applications, 2021)
Activated carbon is a powerful adsorption material which mainly used as pollutants adsorption. The adsorption properties own derived from the main functional groups or chemical atoms derived from the activation processes. In this study, the activated carbon was prepared from waste sago and activated using two different chemicals activation agents called phosphoric acid and potassium hydroxide. The aim of this study was to identify the surface functional group on waste sago activated carbon produced. The results showed that activated carbon with phosphoric acid activator contained OH, C=C, CO and CH functional groups, while activated carbon with potassium hydroxide activator contained O-H, C≡C, C=C, C-O and C-H functional groups. These results lead to support the recommendations for the development of the application of waste sago activated carbon made as adsorbents in the purification of lead (II) and cadmium (II) wastewater.